Understanding dynamic capability as an ongoing concept for studying technological capability - Ahmad Zaidi, Muhammad Faisal; Othman, Siti Norezam (Centre for Promoting Ideas, 2011)
There are numerous conceptual and empirical studies regarding the topics of DCs in the literature.Many literatures have discussing on how to become dynamically capable firms by suggesting the concepts, the antecedents, and the consequences of DCs to achieve performance and sustainable competitive advantage under rapidly changing environment. Meanwhile, the concept of technological management is crucial in studying technological capabilities as it look at the technological capabilities to have important role in deciding the firm success instead of just confined to the study of technology portfolio to create fit with the overall firm objectives. As there is lack of focus of management of technology in this issue and little literature of technology in DCs, the study of technological capabilities as a source of competitive advantage from the concept of DCs is opening for the potential research area.